SEDATION DEPTH DURING CRITICAL CARE TRANSPORT AND HOSPITALIZATION - HAROON, M; SULAIMAN, .; KHAN, MJ; HAQ, IU; AHMAD, S; MALIK, S (Biological and Clinical Sciences Research Journal, 2024)
The purpose of this study was to determine the differences in attained levels of sedation both within intensive care units and collectively regarding overall outcomes when patients were transported outside a hospital either pre-hospital or while being inter-facility transfer by different critical care agencies, having been exposed to light versus deep quality of anaesthesia. After the ethical approval from the institutional review board, this cross-sectional study was conducted at Khyber Teaching Hospital from 01/06/22 to 31/12/22. The primary outcome measure was the relation of starting deep sedation during transport to deep sedation in the first 48 hours after admission (defined as RASS -3 and less). Secondary outcomes included mechanical ventilation duration, inpatient mortality, total hospital stay length of ICU, and delirium within 48 h; coma may also be observed. Final transport RASS in both the study groups was-4.43±0.49 and-1.5±0.5 (p <0.0001). Mean Hospital duration in both study groups was 13.01±4.8 and 35±5.9 days (p<0.0001). A high percentage of inpatient mortality, delirium, and coma cases was seen in the deep sedation group (p<0.0001). The transfer of patient care from the transport team to the hospital team presents a chance to potentially interrupt the progress of treatment and reassess decisions regarding sedation.